Dari Radikal-Ekstrimis ke Moderat Islam: Membaca Pergeseran Faham Moderat pada Kelompok Mantan Teroris di Indonesia - Mujib Ridlwan (LPPM Institut Agama Islam Al-Hikmah Tuban, 2020)
Abstract: This article describes the change in attitude of former terrorists in Lamongan from the causes of being interested in being terrorists to returning from terrorists to individuals who have moderate attitudes. From the results of the study it can be explained that what causes the terrorists to be attracted to terrorism is influenced by friends, family, and people who are identified. His interest is because information that is under by friends, family, and people who characterize is attractive to potential terrorists or individuals who return from terrorists to be moderate. Information that turns individuals into terrorists, including, there is injustice in the hemisphere between Western countries and Muslims, there is a jih kewajiband obligation (fighting with weapons) to groups or people who harm Muslims.